Comparative ecological behaviour of some pre- and post-tsunami isolates of Trichoderma harzianum and T. viride from Andaman & Nicobar Islands (The Journal of Plant Protection Sciences, 2020)
A comparative ecological study of some pre- and post Tsunami isolates of Trichoderma harzianum and T. viride from the Andaman and Nicobar Islands, India, was undertaken to assess the effect on some ecological behavoiur of these biocontrol agents. All the isolates showed better parasitic ability and rhizosphere colonization when the competition of other organisms withdrawn compared to natural and sun dried soil. Both competitive parasitic behaviour and rhizosphere colonization was low inpost-Tsunami isolates of Trichoderma. The chlamydospore inoculum was found best in percentagecolonization of sclerotia of boh R. solani and S. rolfsii, followed by mycelial and conidial inoculum.The isolate ThrAN-5 (T. harzianum) was most efficient in parasitizing the sclerotia of S.
Keywords: Andaman and Nicobar Islands; pre- and post-Tsunami; Trichoderma; rhizosphere colonization; competitive parasitic ability